In silico and in vitro analysis of boAP3d1 protein interaction with bovine leukaemia virus gp51 (2018)
The envelope glycoprotein 51 (gp51) is essential for bovine leukaemia virus (BLV) entry to bovine B-lymphocytes. Although the bovine adaptor protein 3 complex subunit delta-1 (boAP3D1) has been proposed as the potential receptor, the specific ligand-receptor interaction has not yet been completely defined and boAP3D1 receptor and gp51 3D structures have not been determined. This study was thus aimed at a functional annotation of boAP3D1 cellular adaptor protein and BLV gp51 and, proposing a reliable model for gp51-AP3D1 interaction using bioinformatics tools. The boAP3D1 receptor interaction patterns were calculated based on models of boAP3D1 receptor and gp51 complexes’ 3D structures, which were constructed using homology techniques and data-driven docking strategy. The results showed that the participation of 6 key amino acids (aa) on gp51 (Asn170, Trp127, His115, Ala97, Ser98 and Glu128) and 4 aa on AP3D1 (Lys925, Asp807, Asp695 and Arg800) was highly probable in the interaction between gp51 and BLVR domains. Three gp51 recombinant peptides were expressed and purified to validate these results: the complete domain (rgp51), the N-terminal portion (rNgp51) and the C-terminal fragment (rCgp51); and binding assays to Madin-Darby bovine kidney (MDBK) cells were then carried out with each recombinant. It was found that rNgp51 preferentially bound to MDBK cells, suggesting this domain’s functional role during invasion. The rNgp51-MDBK cell interaction was sensitive to trypsin (98% reduction) and chymotrypsin treatment (80% reduction). These results highlighted that the N-terminal portion of gp51 interacted in vitro with the AP3D1 receptor and provides a plausible in silico interaction model. © 2018 Corredor et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.